Goofy vs. Regular: Laterality effects in surfing. Issue 6 (2nd November 2018) - Furley, Philip; Dörr, Jannik; Loffing, Florian
ABSTRACT : The aim of the present study was to test if lateral preferences of surfers are associated with behaviour and performance depending on the direction of a breaking wave. We hypothesized that wave direction and surf stance interact in creating favourable or debilitative performance demands as surfers are either facing the wave (frontside) or the wave is breaking in the back of the surfers (backside). Study 1 was an online survey collecting self-report data of recreational surfers ( n = 394). In Study 2, we analysed all wave scores ( n = 2, 552) and laterality of professional surfers during the season of 2014. Study 1 demonstrated that recreational surfers preferred surfing frontside and described themselves as more skilful when surfing frontside as this is facilitative for picking up visual information. Study 2 did not provide clear evidence that professional surfers on average scored higher during contests when surfing frontside, but when professional surfers had a choice of surfing frontside vs. backside, they were more likely to surf frontside. We discuss the diverging findings between Study 1 and Study 2 from the "circumvention-of-limits" argumentation within the expertise literature as professional surfers most likely have acquired skills allowing them to compensate for debilitative individual and environmental circumstances.